CREATING ARTIFICIAL “STRESS” SITUATIONS IN PRACTICAL SHOOTING EXERCISES (International journal of artificial intelligence, 2024)
This article examines the issue of developing combat readiness skills of personnel by creating artificial stress situations during practical shooting exercises. The study examines the importance of imitating real combat conditions, methods for developing decision-making skills under stress, and methods for increasing the psychological stability of personnel.The article discusses stress situations in creation applicable methodologies , for example , time pressure , unexpected obstacles and complicated conditions create , sound and light from the effects use such as methods analysis will be done . This approach personal of the content fast reaction show , weapons in management accuracy and security to the standards compliance to do qualifications to increase focused .